Corticosteroids Improve Renal Survival: A Retrospective Analysis From Chinese Patients With Early-Stage IgA Nephropathy - Qin, Aiya; Pei, Gaiqin; Tang, Yi; Tan, Li; Wei, Xingfu; Zhong, Zhengxia; Zhou, Ling; Chen, Changyun; Qin, Wei (Frontiers in Medicine, 2020)
Background: The efficacy and safety of corticosteroids and immunosuppressive therapy remains controversial for immunoglobulin A nephropathy (IgAN). This study aims to evaluate the effects of corticosteroid and immunosuppressant therapy in Chinese early stage IgAN patients with estimated glomerular filtration rate (eGFR) >= 45 mL/min/1.73 m2 and proteinuria >= 1 g/24h at biospy. Methods: Patients with biopsy proven IgAN were retrospectively enrolled from 2007 to 2016 from 4 study centers. Patients were regularly followed up for at least 1 year or reached study end point. Patients were categorized into supportive care (SC), steroids alone (CS), and steroids plus immunosuppressant (IT) groups according to treatment regimens. Responses to therapy included complete remission (CR), partial remission (PR), no response (NR) and end stage renal disease (ESRD). The primary end point of this study was defined as a 50% decline in eGFR and/or ESRD. Results: 715 patients (male 47% and female 53%) were recruited and followed for a mean of 44.69 ± 24.13 months. The rate of CR was 81.8%, 62.7%, 37% in CS, IT, SC group, respectively. Renal outcomes were remarkably better in CS group compared with SC and IT group (patients reach end point in each group was 4.6% vs 14.4% vs 11.5%, p=0.001). Moreover, 36-month and 80-month renal survival was significantly better in CS group (98.3% and 86.4 %) than IT (94.2% and 82.4%) and SC (94.0% and 51.6%) group. Early CKD stage disease presented with better kidney survival (p<0.001). Renal survival of CKD stage 1 patients was relatively good despite of different treatment regimens. CS and IT treatment could significant improve renal survival in CKD stage 2 patients when compared with SC group (p<0.001 and 0.007). However, renal survival of CKD stage 3a patients could not be ameliorated by any of the 3 different treatment regimens. Multivariate model showed that hypertension, serum creatinine, E1 and T1/T2 remained as independent predictors of poor renal survival. Conclusions: Corticosteroids in addition to optimal supportive care should be recommended to treat early-stage IgAN patients regarding that it could significantly improve the short-term renal outcome.